Fruits and vegetables at home (FLAM): a randomized controlled trial of the impact of fruits and vegetables vouchers in children from low-income families in an urban district of France - Camille Buscail; Aurore Margat; Stéphanie Petit; Judith Gendreau; Paul Daval; Pierre Lombrail; Serge Hercberg; Paule Latino-Martel; Aurélie Maurice; Chantal Julia (BMC, 2018)
Abstract Background Fruits and Vegetables (FV) consumption is considered a marker of social inequalities in health since it is considerably decreased in disadvantaged populations. The main objective of this trial was to evaluate the impact of vouchers for FV purchase on the consumption of FV among children living in disadvantaged families in a French urban district. Methods The FLAM study was a controlled randomized intervention trial, performed in Saint-Denis (North suburbs of Paris). The study group (intervention or control) was randomly attributed to parent-child pairs at inclusion. The intervention group received vouchers exchangeable for FV over a 1 year period. Nutritional education through workshops was available for both groups. FV consumption was assessed through face-to-face food frequency questionnaires. Participants who reported eating less than 3.5 FV per day were considered low FV consumers. Results A total of 92 parent-child pairs were included, in which 45 were allocated to the intervention group and 47 to the control group. Amongst them, 64 completed the final follow-up questionnaire (30% lost to follow-up). After one year, the proportion of low FV consumers in children was significantly lower in the intervention group (29.4%) compared to the control group (66.7%, p = 0.005). Overall, 82% of the vouchers were used by the families. Conclusions This study found a decreased proportion of small consumers in children after 1 year of distribution of FV vouchers compared to the control group. FV vouchers could be an effective lever to increase FV consumption among children from disadvantaged households. Trial registration ClinicalTrials.gov identifier no. NCT02461238.